2016
DOI: 10.5539/jmsr.v5n2p100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Process Parameters on the Surface Roughness during turning operation of High Strength Steel

Abstract: High strength steels are used in many high-end applications. Due to the high cost of raw material, manufacturing engineers should be very careful during their machining process. Surface finish is the critical factor in the turning process of combustion chambers of gun barrels. It should conform to the required accuracy values. This paper analyzes the impact and parameters of the process have on the roughness of the surface. The impact is analyzed during turning operations of high strength steel material. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In anticipation of the next sixth technology revolution, it is becoming an increasingly important technique for processing large data sets using artificial intelligence and the integration of artificial intelligence algorithms in automated production. Many previous investigations have been devoted towards developing prediction models for rough turning [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Risbood et al [1] researched and produced models for forecasting roughness and dimensional deviation for dry and wet turning of mild steel rods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In anticipation of the next sixth technology revolution, it is becoming an increasingly important technique for processing large data sets using artificial intelligence and the integration of artificial intelligence algorithms in automated production. Many previous investigations have been devoted towards developing prediction models for rough turning [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Risbood et al [1] researched and produced models for forecasting roughness and dimensional deviation for dry and wet turning of mild steel rods.…”
Section: Introductionmentioning
confidence: 99%
“…Tootooni et al [18] reported surface roughness using a noncontact measurement method during the turning process. Abbas [19] analyzed the effect of the feed rate, depth of cut and cutting speed on the surface roughness in turning high-strength steel. Though all the previously mentioned research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] provided prediction models of surface roughness, they failed to solve the problem of determining the optimal cutting parameters for the minimum surface roughness and maximum production rate.…”
Section: Introductionmentioning
confidence: 99%